Table S1 from Analysis of Several Common APOBEC-type Mutations in Bladder Tumors Suggests Links to Viral Infection - Nina Rao (15321199) (2025)
Table S1: Patient summary of demographic characteristics and mutation status in individual sets and the combined BC set